2009
DOI: 10.1158/0008-5472.can-09-1208
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to Skin Carcinogenesis in TREX2 Knockout Mice

Abstract: TREX2 is a proofreading 3 ¶-5 ¶ exonuclease that can be involved in genome maintenance; however, its biological role remains undefined. To better understand the function and physiologic relevance of TREX2, we generated mice deficient in TREX2 by targeted disruption of its unique coding exon. The knockout mice are viable and do not show relevant differences in growth, survival, lymphocyte development, or spontaneous tumor incidence compared with their wild-type counterparts over a period of up to 2 years. Also,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 44 publications
(54 reference statements)
2
58
0
Order By: Relevance
“…TREX1 and TREX2 have similar homodimeric structures with distinct elements that point to different biological roles (19,20). Deletion of the TREX2 gene in mice increases susceptibility to induced skin carcinogenesis (21), contrasting the autoimmune phenotype of the TREX1 knock-out mouse. The TREX1 dimer has an 8-amino acid polyproline II helix on the top and bottom of the front face and the TREX2 dimer has a ␤-hairpin in the same position.…”
Section: R114hmentioning
confidence: 99%
See 1 more Smart Citation
“…TREX1 and TREX2 have similar homodimeric structures with distinct elements that point to different biological roles (19,20). Deletion of the TREX2 gene in mice increases susceptibility to induced skin carcinogenesis (21), contrasting the autoimmune phenotype of the TREX1 knock-out mouse. The TREX1 dimer has an 8-amino acid polyproline II helix on the top and bottom of the front face and the TREX2 dimer has a ␤-hairpin in the same position.…”
Section: R114hmentioning
confidence: 99%
“…5A, lanes [21][22][23][24][25][26] exhibit no detectable dsDNA degradation activity. However, the TREX1 R114H/D201ins (Fig.…”
Section: The Trex1mentioning
confidence: 99%
“…Interestingly, the DNA exonuclease TREX2 is one of the genes that is most highly enriched in psoriatic lesions compared to normal skin (Li et al, 2014). Furthermore, TREX2 expression is restricted to keratinocytes, where it contributes to approximately half of the 3'-exonuclease activity of the epidermis (Parra et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in heterologous cellular systems have shown that TREX2 may condition several DNA repair mechanisms (Aubert et al, 2014;Bennardo et al, 2009;Hu et al, 2013). Interestingly, neither spontaneous tumors nor chromosomal instability have been observed in Trex2 -/-mice (Parra et al, 2009). However, TREX2 deficiency in mice leads to increased susceptibility to carcinogeninduced skin tumorigenesis (Manils et al, 2015;Parra et al, 2009), indicating a critical role for this exonuclease in the skin homeostasis upon DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…We could exclude that this degradation depends on DNase1, which is also expressed in differentiating keratinocytes 23 . Other candidate contributors to cornification-associated DNA fragmentation include, but are not limited to, caspase-activated DNase (CAD), also known as DNA fragmentation factor B 24 and the exonuclease TREX2 10,25,26 . Like in suppression of DNA breakdown during programmed cell death of hair and nail keratinocytes 14 and sebocytes 15 , the blockade of DNA degradation by deletion of DNase1L2 and DNase2 prevented the complete removal of histone H3, a component of nucleosomes, whereas the inter-nucleosomal histone H1 and a nuclear protein without DNA interaction, lamin A/C, were degraded.…”
Section: Discussionmentioning
confidence: 99%